Hubungan Lamanya Pemakaian KB Implant dengan Kenaikan Berat Badan di Wilayah Kerja Puskesmas Taniwel - Silvia Fransina Sopacua; Kamidah Kamidah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Implant is a contraceptive method that only contains progestin with a long working period. The effect of the hormone progesterone facilitates the conversion of carbohydrates and sugars into fat, so that fat under the skin increases, in addition, the hormone progesterone also causes increased appetite and decreases physical activity, as a result, the use of implants can cause weight gain. Continuous weight gain can cause obesity. Objective: to determine the relationship between the duration of use of contraceptive implants and weight gain. Method: quantitative research with a cross-sectional approach. This study was conducted in June 2024. The population of Implant acceptors amounted to 56 people, the sampling technique used total sampling. the analysis test used chi square. Results: Respondents with a duration of use <2 years as many as 17 respondents, the majority did not experience weight gain, namely 13 respondents (23.2%). Respondents with a duration of use of implants ≥ 2 years as many as 39 respondents, the majority experienced weight gain, namely 24 respondents (42.9%). Data analysis obtained 0.009 <0.05 Conclusion: There is a relationship between the length of implant use and weight gain in the Taniwel Health Center work area